Maize farmers’ use, preference, and trustworthiness of information sources and communication channels in Dormaa, Ghana: A gender comparison. - Namah Taku-Forchu; Shuyang Qu; Misty D Lambert; Michael S. Retallick; Jonathan D Ulmer; George P. Opit (Journal of Applied Communications, 2023)
The study aimed to identify maize farmers' use, preference, and trustworthiness of the various information sources and communication channels farmers in Dormaa, Ghana, used to receive information about their farming activities. A questionnaire was developed, and data was collected from 217 maize farmers. The result revealed more males are involved in maize production than females. Most males indicated they received training in using hermetic bags more than female farmers. Respondents ranked Extension agents highest as the source from which they receive their farming information. Based on the level of preference for the information sources, the results show a statistically significant difference between male and female farmers' preference for Extension agents, friends/neighbors, and church leaders, with male farmers preferring these information sources more than females. The result indicated a significant difference between male and female preferences for phone calls, with more males indicating they preferred telephone calls. The t-test results of farmers’ trustworthiness for the information sources revealed a significant difference between male and female farmers’ trustworthiness for fellow farmers, friends/neighbors, telephone calls, and posters/billboards for communication channels. Given that Extension professionals are the most preferred and trustworthy source of information, we recommend that the government and stakeholders organize extension training programs to strengthen local extension. We recommend greater women involvement and given strategic roles in the planning and organization of training programs.
Keywords: Gender; information sources; preference; trustworthiness; Ghana